Composite, multilayer and three-dimensional substrate supported tin-based electrodeposits from methanesulphonic acid. (3rd May 2016) - Walsh, Frank C.; Low, C. T. J.
Abstract : Tin and tin–alloy deposits enjoy many applications in the electronics, tribology and engineering industries with potential applications as electrodes for lithium batteries and as electrocatalyst coatings. Methanesulphonic acid (MSA) has become a favoured electrolyte due to its environmental benefits and ability to offer a vehicle for many metal alloy, conductive polymer and composite coatings. A number of emergent uses require less common compositions or structures of alloy, polymer or composite deposits. This paper concisely provides diverse examples of modern tin-containing deposits from aqueous MSA, including Sn–Cu alloys having a very wide composition together with a wide range of colours (golden-yellow–dark-brown) and surface finishes, a Sn–Cu composite deposit containing ceramic, protonated titanium oxide nanotubes for batteries, a tin–copper–bismuth ternary alloy and tin deposits supported on an inert reticulated vitreous carbon or carbon felt substrate to provide a porous, three-dimensional tin surface for electrocatalysis and batteries. The importance of controlled current distribution and electrode/electrolyte movement is illustrated by the use of the rotating disc electrode, rotating cylinder electrode and rotating cylinder Hull cell.